Perceptions of physical education teachers on obstacles and pedagogy competencies in online learning - Purnomo, Eddy; Virama, La Ode Adhi; Ries, Francis; Naviri, Sinta; Fauzi, Fauzi (Jurnal Pendidikan Jasmani Indonesia, 2023)
This research aimed to determine the perception of junior high school physical education teachers on obstacles and pedagogical competencies during online learning. Quantitative method supported with a survey approach were used in this research. The research data were analyzed using average value and standard deviation. The data were then compared using MANOVA. The results showed that junior high school physical education teachers perceived all possible obstacles to online learning. Based on the analysis of the average value using the Likert scale on the Google Form questionnaire, it can be ascertained that the highest rank is based on the obstacle factor, namely Absence of Real Time Feedback (M= 2.66; SD= 0.76); Motivation and Commitment (M= 2.46; SD= 0.78); Engaging Student (M= 2.46; SD= 0.70); Flexibility and Delivery Mode (M= 2.37; SD= 0.69); Lack of Feedbacks (M= 2.34; SD= 0.59).  Meanwhile, the results of research on pedagogical competencies showed that in general, physical education teachers in junior high schools had good perceptions of all pedagogical competencies. The MANOVA results showed that there was no significant difference between gender, obstacles, and pedagogical competences of physical education teacher during online learning. The findings categorize the top three barriers perceived by physical education teachers: absence of real time feedback, motivation and commitment, and engaging student. The results of the demographic analysis on gender showed that there were no significant differences between technological factor, individual factor, pedagogical factor, and enabling conditions.